Factor XIII deficiency in the Saudi population, an underestimated bleeding risk. Review article and an illustrative case report with dental complications - Mansour Aljabry (Elsevier, 2023)
Introduction: Congenital Factor (F) XIII deficiency is an autosomal recessive disorder caused by genetic variations in either F13A or F13B genes leading to a bleeding diathesis with variable severity. Patients with severe FXIII deficiency usually present with umbilical cord bleeding during the neonatal period. Ecchymosis, epistaxis, and post-trauma bleeding are the most frequently reported features in FXIII deficiency. Poor wound healing and recurrent delayed bleeding episodes are typical features of factor XIII deficiency as well. Diagnosis of FXIII deficiency can be made only with a high index of clinical suspicion and sets of FXIII-directed assays, as all primary coagulation tests are typically normal. Objectives and methodology: This focused review sheds light on the key points related to FXIII deficiency in the Saudi population, focusing on the clinicopathological and therapeutic aspects highlighted with an illustrative case report incidentally diagnosed during a dental procedure. Results and conclusion: The disorder is apparently underdiagnosed and underreported in the Saudi population, as only 49 cases of congenital FXIII deficiency have been reported. Moreover, no single case report of acquired FXIII deficiency has been reported in the population.